2000
DOI: 10.4278/0890-1171-15.2.89
|View full text |Cite
|
Sign up to set email alerts
|

The Social Context of Experimenting with Cigarettes: American Indian “Start Stories”

Abstract: Smoking rates among American Indians are higher than any other racial or ethnic group. Focus groups were conducted with 140 American Indian middle school students who were not living on reservations to explore the social context of smoking initiation. Most teens smoked their first cigarettes with friends, siblings or cousins, usually out of curiosity, or in response to peer encouragement. There was no indication of any link between smoking initiation and use of tobacco in traditional ceremonies. Overall, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…Further, an impact of the obligation to change smoking behavior on patterns of social activity was consistently reported. The importance of smoking in the social realm has been observed in other settings, and social support is a known aid to quitting [39-42]. The alteration of associated social patterns that accompanies smoking cessation has been reported and usually incurs a sense of loss as was often the case among the women we interviewed [42].…”
Section: Discussionmentioning
confidence: 80%
“…Further, an impact of the obligation to change smoking behavior on patterns of social activity was consistently reported. The importance of smoking in the social realm has been observed in other settings, and social support is a known aid to quitting [39-42]. The alteration of associated social patterns that accompanies smoking cessation has been reported and usually incurs a sense of loss as was often the case among the women we interviewed [42].…”
Section: Discussionmentioning
confidence: 80%
“…From this perspective, because tobacco use encompasses human behavior and the social context within which such behavior is practiced, 65,66 curbing the use and spread of tobacco demands different measures that reinforce each other. While ideas on tobacco control legislation (to prevent youth smoking) began in the 1980s, health warnings on cigarette packages and advertising bans began from the 1960s in developed countries.…”
Section: Resultsmentioning
confidence: 99%
“…Later studies (16,21,42) note that adolescents are adept at locating stores and clerks that will sell tobacco products to underage purchasers. Importantly, Kegler, Cleaver, and Kingsley (2000) note that no American Indian youth in their study spoke of buying their first cigarette. This finding was borne out in many studies.…”
Section: Access/sales Issuesmentioning
confidence: 93%
“…Studies, especially DiFranza and Coleman (2001) and Kegler, Cleaver, and Kingsley (2000), detailed a multiplicity of sources and strategies used by adolescents for obtaining cigarettes even in high-enforcement localities. For example, an earlier study (31) reported that ".…”
Section: Access/sales Issuesmentioning
confidence: 99%